Fiscal expenditures, revenues and labour productivity in South Africa - Andrew Phiri; Chuma Mbaleki (Cogent Economics & Finance, 2022)
The COVID-19 pandemic emerged at a time when the South African economy was already battling to recover from the aftermath of the global financial crisis of 2007-09 which led the country to experience a decade-old slowdown in labour productivity. Our study investigates the role which government plays in influencing labour productivity by estimating a log-linearized growth model augmented with a fiscal sector using the autoregressive distributive lag model applied to annual data of 1990-2020. We further disaggregate the composition of government size into seven expenditure items and six revenue items, and find i) education, health, recreation and public safety to be expenditure items most beneficial to short-run and long-run labour productivity ii) income taxes and VAT to be revenue items most beneficial to long-run productivity and yet most taxes have adverse short-run effects. The policy implications of the study are discussed.
Keywords: 330; public expenditure; fiscal revenues; labour productivity; ARDL; South Africa